The Development and Character of Foreign Investment in Late Colonial Indonesia - Mark van de Water (Lembaran Sejarah, 2018)
This contribution discusses the development of private foreign investment in late colonial Indonesia. The increase in numbers of individual firms, their expanding volume and accumulation of investment in the Netherlands Indies are shown. The focus is on the years 1910-1940 and on Dutch foreign investment, although investment by other countries is touched upon in passing. The data used for this article originate from a database compiled from the Handboek voor cultuuren handelsondernemingen in Nederlandsch-Indië (Handbook for cultivation and trading companies in the Netherlands Indies) and will also be incorporated into my PhD dissertation entitled ‘Foreign investment and colonial economic growth in Indonesia’, which forms part of the larger research project ‘Foreign capital and colonial development in Indonesia’.